Menelusuri Transmisi Gereja Masehi Advent Hari Ketujuh Di Indonesia - Wawan Hernawan (UIN Sunan Gunung Djati Bandung, 2016)
Advent is a denomination in Christianity. Historically, denomination was a sect of Protestant Christianity Church when Christianity had no power to control Advent. Increasingly Advent separated its self from, and did not want to come back to, Christianity. The development of Advent movement spread all over the world. To spread their religious teaching, Adventists organized the forceful zending in Indonesia that was centered in Jakarta for western region and in Manado for eastern, with the name Gereja Masehi Advent Hari Ketujuh di Indonesia (The Seventh-day Advent Christianity Church in Indonesia). The aim of exploring this Advent Church is to reconstruct the growth and development of the advent movement. Here is used a method of history research which includes four stages of history method; heuristic, critic, interpretation and historiography. Meanwhile, to get the explanation of the research problem, it is used a perspective of multi dimensions